Reynolda Manor Branch Library during a summer children's program. - Unknown (Forsyth County Public Library, 1990)
Photo made in the 1990s.
Reynolda Manor Branch Library during a summer children's program.
Keywords: Forsyth County (N.C.) -- History -- Sources; Winston-Salem (N.C.); Forsyth County Public Library; Digital Forsyth; Forsyth County (N.C.) -- History -- Pictorial works